Breastfeeding challenges among Thai adolescent mothers: hidden breastfeeding discontinuation experiences - Sasitara Nuampa (2022)
Purpose: The purpose of this study was to explore the experiences of adolescent mothers who wean their babies from breastfeeding before the first six months from the perspective of a psychosocial aspect in the Thai context. Design/methodology/approach: A descriptive qualitative design was applied to this study to obtain meaningful data. The adolescent mothers for the primary study and nine supplementary participants were recruited from the largest university hospital in Bangkok, Thailand. Semi-structured in-depth interviews were conducted with 20 adolescent mothers. Descriptive statistics and content analysis were used for data analysis. Findings: The average breastfeeding duration was 3.1 months while breastfeeding exclusively lasted 1.3 months. More than half of the adolescent mothers encountered breastfeeding problems at hospitalization including sore/cracked nipples (63.6%), one side breastfeeding (27.3%) and exhaustion (9.1%). According to the content analysis, (1) breastfeeding obstacles concealed by the adolescents' dependence and (2) repetitive emotional mistakes encountered were the two main themes that emerged. Originality/value: The influence of key family members plays a vital role in breastfeeding and psychological outcomes. Therefore, family-adolescent support programs including support from the adolescents' mothers and grandmothers may improve breastfeeding outcomes, yield positive emotions and enhance maternal attachment. Moreover, healthcare professions are important mediators to convince adolescent mothers' key family members to reach an agreement and provide suitable support.